Happy Howl-oween! - Stephens, Elle; Batson, Alan (2021)
Join Tag, Scooch, and all their friends as they celebrate Howl-oween in Pawston!
Cover title.
On board pages.
"A Netflix original series"--Cover.
Keywords: Dogs -- Juvenile fiction; Halloween -- Juvenile fiction; Board books; Dogs -- Fiction; Halloween -- Fiction; Dogs; Halloween; Board books; Fiction; Juvenile works